Genetically determined serum bilirubin level and the risk of heart failure: A mendelian randomization study - Guan, Bo; Yang, Mingyan; Shen, Xing; Wang, Yemei; Liu, Yutong; Liu, Ruihan; Li, Shijun; Cao, Jian (Frontiers in Genetics, 2023)
Background: The association between serum bilirubin level and heart failure (HF) was controversial in previous observational studies and the causal effects of bilirubin on HF have not been investigated. Here, we conducted a Mendelian randomization (MR) study to investigate the associations between genetically determined bilirubin level and HF. Methods: Summary data on the association of single nucleotide polymorphisms (SNPs) with serum bilirubin levels were obtained from genome-wide association study (GWAS) for individuals of European descent and East Asian descent separately. Statistical data for gene-HF associations were extracted from three databases: the HERMES Consortium (47,309 cases and 930,014 controls), FinnGen study (30,098 cases and 229,612 controls) for European population and Biobank Japan (2,820 HF cases and 192,383 controls) for East Asian population. We applied a two-sample Mendelian randomization framework to investigate the causal association between serum bilirubin and HF. Results: Findings from our MR analyses showed that genetically determined serum bilirubin levels were not causally associated with HF risk in either European or East Asian population (odds ratio [OR] = 1.01 and 95% confidence interval [CI] = 0.97–1.05 for HERMES Consortium; OR = 1.01 and 95% CI = 0.98–1.04 for FinnGen Study; OR = 0.82, 95% CI: 0.61-1.10 for Biobank Japan). These results remained unchanged using different Mendelian randomization methods and in sensitivity analyses. Conclusion: Our study did not find any evidence to support a causal association between serum bilirubin and HF.